Computational thinking : a beginner's guide to problem-solving and programming - Beecher, Karl, ....- (Swindon : BCS Learning & Development Limited, 2018)
Computational thinking (CT) is a timeless, transferable skill that enables you to think more clearly and logically, as well as a way to solve specific problems. With this book you'll learn to apply computational thinking in the context of software development to give you a head start on the road to becoming an experienced and effective programmer.
Keywords: Informatica; Programmeren